2022
DOI: 10.1186/s41039-022-00201-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of extreme weather on student online learning participation

Abstract: In March 2020, the COVID-19 pandemic forced over 1 billion learners to shift from face-to-face instruction to online learning. Seven months after it began, this transition became even more challenging for Filipino online learners. Eight typhoons struck the Philippines from October to November 2020. Two of these typhoons caused widespread flooding, utilities interruptions, property destruction, and loss of life. We examine how these severe weather conditions affected online learning participation of Filipino st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Students and their families may experience severe financial hardship due to natural disasters, resulting in property damage, lost income, and increased costs for recovery and reconstruction. Lagmay and Rodrigo [ 63 ] reported that extreme weather occurrences cause physical and financial harm, which negatively affects academic success. Young children from economically challenged households have less parental involvement and financial support for their schooling, which leads to a performance difference that widens with time.…”
Section: Discussionmentioning
confidence: 99%
“…Students and their families may experience severe financial hardship due to natural disasters, resulting in property damage, lost income, and increased costs for recovery and reconstruction. Lagmay and Rodrigo [ 63 ] reported that extreme weather occurrences cause physical and financial harm, which negatively affects academic success. Young children from economically challenged households have less parental involvement and financial support for their schooling, which leads to a performance difference that widens with time.…”
Section: Discussionmentioning
confidence: 99%
“…Research also focused on educational impacts and university support provisions. Overall, research on academic outcomes for students following a disaster was less pronounced (Breen and Meyer 2021;Di Pietro 2018;Doyle et al 2017;Lagmay and Rodrigo 2022). It is imperative to study the effect that disasters have on students' academic performance because without understanding the entire scope it will be difficult to apply the proper interventions and educational strategies to protect students' academic progress when it is disrupted by disasters.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in our analysis focused on how various disasters disrupt or shape academic outcomes, shedding light on the intricate interplay between these external forces and students' pursuit of knowledge (Breen and Meyer 2021;Carales and Lopez 2022;Collings et al 2018;Di Pietro 2018;Lagmay and Rodrigo 2022;Sholes et al 2023). Several aspects of a student's academic experience in higher education have been found to be impacted by disasters.…”
Section: Educational and Academic Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Online learning is that students learn in virtual space through electronic devices and networks. E-learning is also called digital learning, and its basic elements are digital learning environment, digital learning resources and digital learning methods [2]. The difference between online learning participation and learning participation is the learning environment of students.According to Hrastinski, online learning participation refers to the complex process of students' learning by participating in and maintaining relationships with others, which is manifested in students' behavior, communication, thinking, feeling and belonging in the process of online and offline learning.Although students' learning environment has changed, the nature of students' participation in learning has not changed.…”
Section: Online Learning Engagementmentioning
confidence: 99%